Catástrofes Mistas. Uma perspetiva ambiental - Luciano Lourenço (Riscos e Catástrofes, 2019)
The mixed risks, of environmental component, are associated with a potentially hazardous phenomenon with combined causes, that is, for its manifestation compete natural conditions and anthropic actions. In this book, more than a dozen risks are analyzed, which are part of two main typologies: the mixed risks of atmospheric component, mainly associated with changes in the chemical composition of the atmosphere, and the mixed risks of geodynamic component, which relate to forces and processes that act on the Earth (internal geodynamics, for example the risk of induced seismicity, and external geodynamics, with emphasis on the risks of erosion, desertification, salinisation, pollution and forest fires). In all risk typologies, here we analyzed, the contribution of the human being, through its actions and activities, constitutes a common element, extending, unambiguously, its causes and consequences. Therefore, all authors are unanimous about the need to implement integrated measures and actions to safeguard the main natural resources.